1989
DOI: 10.1111/j.1471-4159.1989.tb11762.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐N‐Oxalylamino‐L‐Alanine Action on Glutamate Receptors

Abstract: beta-N-Oxalylamino-L-alanine (L-BOAA) is a non-protein excitatory amino acid present in the seed of Lathyrus sativus L. This excitotoxin has been characterized as the causative agent of human neurolathyrism, an upper motor neuron disease producing corticospinal dysfunction from excessive consumption of the lathyrus pea. Previous behavioral, tissue-culture, and in vitro receptor binding investigations revealed that L-BOAA might mediate acute neurotoxicity through quisqualate (QA)-preferring glutamate receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 22 publications
(14 reference statements)
1
41
0
Order By: Relevance
“…BMAA (an iGluR agonist) might inhibit AtGLR function but via a different mechanism. In animal systems, non-native agonists such as BMAA, can impair iGluR function because often iGluRs remain sensitized to these non-native ligands (Ross et al, 1989). In contrast, animal iGluRs become desensitized to the native agonist, Glu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMAA (an iGluR agonist) might inhibit AtGLR function but via a different mechanism. In animal systems, non-native agonists such as BMAA, can impair iGluR function because often iGluRs remain sensitized to these non-native ligands (Ross et al, 1989). In contrast, animal iGluRs become desensitized to the native agonist, Glu.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the targets of AtGLR function in plants, we tested whether other compounds known to block iGluR function in animals could also block aspects of Ara-bidopsis growth and development. Several of these iGluR agonists are plant-derived products: kainate (KA; Monaghan et al, 1989;Bettler and Mulle, 1995) made by seaweed (Digenea simplex); ␤-N-oxalylamino-l-alanine (Ross et al, 1989) made by chickpeas (Lathyrus sp. ), and BMAA (Copani et al, 1991) made by cycads.…”
mentioning
confidence: 99%
“…In contrast to BMAA, BOAA ingestion in animals and humans could induce neurodegeneration in a condition called neurolathyrism, but this disorder does not resemble ALS-PDC (Ross et al 1989). Similarly, neither cycasin nor MAM give ALS-PDC-like phenotypes (for a review, see Kurland 1972).…”
Section: Introductionmentioning
confidence: 99%
“…17 The increase of glutamate may, in turn, cause competitive inhibition of high-and low-affinity glutamate transport, which is supposed to be a primary mechanism by which neurotransmitters are removed from the synaptic cleft. 17,35,36 Studies have shown that there is an interdependence among various associated receptor systems within the CNS, 18 hence further studies were carried out to investigate the effect of long-term administration of lathyrus on dopamine, cholinergic and benzodiazepine receptors. Rats exposed to 50% low or high toxin lathyrus diet and guinea pigs exposed to 50% or 80% lathyrus diet were found to have a significant increase in [ 3 H]spiperone binding to striatal regions, which may be playing a role in modulating the motor behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In vitro studies have shown that β-L-ODAP selectively binds to the non-N-methyl-D-aspartate (non-NMDA) glutamate receptors, which are of α-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) or quinsqualate (QA) type and inhibit the low and high glutamate uptake systems in synaptosomes. 17,18 Oral administration of nonconvulsant doses of β-L-ODAP to rats increases the cerebellar cyclic guanosine monophosphate (cGMP) level and induces downregulation of non-NMDA glutamate receptors in the frontal cortex. 19,20 However, little is known about the cellular mechanism of β-L-ODAP excitotoxicity on glutamate and other related neuroreceptors on systemic administration of lathyrus pulse.…”
Section: Introductionmentioning
confidence: 99%